Pengaruh Pendidikan Kesehatan Berbasis Digital terhadap Tingkat Pengendalian Hipertensi Dirumah Sakit Islam Pati - Syaroful Anam; Feri Catur Yuliani; Yeni Rusyani (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Background: Hypertension is a non-communicable disease often referred to as a silent killer because it is often asymptomatic but has the potential to cause serious complications such as stroke and heart failure. According to the Basic Health Research (Riskesdas) (2023), the prevalence of hypertension in Indonesia reached 35.2%. Digital-based health education is considered capable of improving patient knowledge, compliance, and blood pressure control. Methods: This study used a quasi-experimental pretest–posttest with a control group design. Sixty respondents were divided into intervention and control groups. Data analysis used paired t-tests and independent t-tests. Results: The average blood pressure in the intervention group decreased from 152.3/94.0 mmHg to 135.4/84.1 mmHg (p = 0.002 and p = 0.005), while in the control group there was only a small decrease. Conclusion: Digital-based health education has a significant impact on hypertension control by increasing patient knowledge and compliance.